May Irwin : singing, shouting, and the shadow of minstrelsy - Ammen, Sharon, 1951- (Music in American life., 2017)
"Before Sophie Tucker "corked up" to entertain her audiences with ragtime songs in Negro dialect, and before Fanny Brice stumbled into the footlights in her rendition of the "Dying Swan," May Irwin (1862-1938) was the reigning queen of comedy and "coon" songs on the American stage. This project, the first serious study of May Irwin, traces the comedic performer's colorful and successful career and also examines the strategies that Irwin employed to maintain both popularity and power while stepping far outside traditionally defined boundaries of late nineteenth-century womanhood. Ammen considers the content and style of Irwin's comedy; her repertoire and status as a "coon shouter"; her position as a celebrated cook and homemaker; and her social and political activities. Irwin's career began as a singing act with her younger sister, Flora, when May was 12. The Irwin Sisters achieved enough success over the next few years to gain a regular spot at Tony Pastor's popular theatre in New York City. After six years with Pastor, May, then 21, struck out on her own and went to work for Augustin Daly's stock company, where she developed her comedic and improvisational skills. By the 1890s she was established as a star on the vaudeville circuit as well as the legitimate stage and a few films. In addition to her theatrical work, both onstage and as a manager, Irwin was also known as an accomplished homemaker and loving mother; a political activist; a real estate tycoon; a prolific composer of songs; and the writer of many articles as well as a popular cookbook"--